2004
DOI: 10.1093/alcalc/agh116
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF ACETALDEHYDE AND TNFα ON THE INHIBITORY KAPPA B- Α PROTEIN AND NUCLEAR FACTOR KAPPA B ACTIVATION IN HEPATIC STELLATE CELLS

Abstract: TNFalpha and acetaldehyde independently activate NF-kappaB by rapid enhancement of IkappaB-alpha kinase activity and degradation of IkB-alpha protein. Increased TNFalpha is the principal mechanism for the elevation of NF-kappaB in severe alcoholic hepatitis. The elevation of NF-kappaB due to TNFalpha enhance liver injury, but inhibit fibrogenesis. In contrast, the effect of acetaldehyde in activating NF-kappaB is associated with increases in both liver injury and fibrogenesis, indicating that the effects of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Previous in vitro studies have suggested that acetaldehyde can increase TNFα production in both HepG2 cells and Kupffer cells (Hsiang et al, 2005; Cao et al, 2002). Since significant in vitro data from previous studies suggest a role for acetaldehyde in EtOH-mediated increases in TGFβ and stellate cell activation (Anania et al, 1996; Purohit and Brenner, 2006; Novitsky et al 2005; Zheng et al, 2007), it is surprising that 4MP treatment had no effect in the current study on EtOH-induced TGFβ mRNA or increased expression of SMA. Acetaldehyde has also been reported to inhibit hepatocyte proliferation in vitro (Clemens, 2007).…”
Section: Discussionmentioning
confidence: 59%
“…Previous in vitro studies have suggested that acetaldehyde can increase TNFα production in both HepG2 cells and Kupffer cells (Hsiang et al, 2005; Cao et al, 2002). Since significant in vitro data from previous studies suggest a role for acetaldehyde in EtOH-mediated increases in TGFβ and stellate cell activation (Anania et al, 1996; Purohit and Brenner, 2006; Novitsky et al 2005; Zheng et al, 2007), it is surprising that 4MP treatment had no effect in the current study on EtOH-induced TGFβ mRNA or increased expression of SMA. Acetaldehyde has also been reported to inhibit hepatocyte proliferation in vitro (Clemens, 2007).…”
Section: Discussionmentioning
confidence: 59%
“…Acetaldehyde has also been shown to affect NFκB-induced cytokine production in various liver cells. In the presence of acetaldehyde, Kupffer cells, the specialized macrophages in the liver, treated with LPS show decreased NFκB activation (Jokelainen, Thomas et al 1998), while hepatic stellate cells, the major producers of collagen that accumulate during hepatic fibrosis, show enhanced NFκB activation (Novitskiy, Ravi et al 2005). Finally, acetaldehyde disrupts intestinal epithelial barrier function and increases paracellular permeability which plays a crucial role in the pathogenesis of alcoholic liver disease by a tyrosine kinase-dependent mechanism (Sheth, Seth et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…SREBP-1c knockout mice fed ethanol had the expected levels of proapoptotic factors, suggesting that CHOP, and the ER stress response, independently of SREBP-1c, play the major role in ethanol-induced apoptosis. Although there are reported correlations between TNF-␣ levels and SAH/SAM ratios after chronic ethanol feeding (43), TNF-␣ receptor (TNFR1) knockout mice were not protected against the ER stress response and responded to betaine administration the same as wild-type mice (32). Thus, homocysteine/ER stress pathways probably play a significant role in ethanol-induced liver disease synergistically with TNF-␣.…”
Section: Homocysteine and The Er Stress Responsementioning
confidence: 97%